Age Estimation Using Demirjian Eight Teeth Method of Right Maxillary Third Molar (18) And Mandibular Third Molar Teeth (48) - Swetha Ramasubramanian, Dr. Abirami Arthanari (Drugs and Cell Therapies in Hematology, 2021)
Introduction: Estimation of age of an individual can be carried out by evaluating the pattern of dental development. Demirjian’s grading of tooth calcification is widely used to assess the age of individuals with developing dentitions.The tooth with its developmental stages provides us with a non-invasive modality to estimate the age of the person. Aim: To estimate age using Demirjian 8 teeth method of right maxillary third molar and right mandibular 48. Materials and Methods: A total of 200 (male-100, female-100) Orthopantomogram (OPGs) were collected from the radiology department of Saveetha Dental College. Age estimation done using Demirjian 8 method of right upper and lower wisdom tooth(18, 48). Age criteria 10.1 - 20.The results were correlated using chi square analysis in SPSS software. Results: The p values of staging of maxillary third molar (18) in males showed 0.343 > 0.05, staging of mandibular third molar (48) in males showed 0.533 > 0.05, staging of 18 in females showed 0.612 > 0.05 and staging of 48 in females showed 0.661 indicating statistically insignificant. Conclusion: The age estimation using this method was not efficient for staging of 18 and 48 in males and females.